Energy allocation trade-offs as a function of age in fungiid corals - Grinblat, Mila; Eyal-Shaham, Lee; Eyal, Gal; Ben-Zvi, Or; Harii, Saki; Morita, Masaya; Sakai, Kazuhiko; Hirose, Mamiko; Miller, David J.; Loya, Yossi (Frontiers in Marine Science, 2023)
To compete effectively, living organisms must adjust the allocation of available energy resources to growth, survival, maintenance, and reproduction during their life history. Their energetic demands and allocations change throughout the life history of an organism, and understanding energy allocation strategies requires determination of the relative age of individuals. As most scleractinian corals are colonial, relationships between age and mass/size are complicated by colony fragmentation, partial mortality and asexual reproduction. To overcome these limitations, the solitary mushroom corals - Herpolitha limax from Okinawa, Japan and Fungia fungites from Okinawa and the Great Barrier Reef (GBR), Australia - were used to investigate how energy allocation between those fundamental processes varies as a function of age. Measuring relative growth, biochemical profiles, and fecundity of individuals in different weight groups, and the settlement success of their progeny, revealed physiological trade-offs between growth and reproduction, with increasing body mass leading ultimately to senescence. In the present study, the smallest individuals of both species studied were found to invest most of their energy in relative growth, showing higher lipid and carbohydrate contents. In medium sized corals, this pattern was overturned in favour of reproduction, manifesting in terms of both higher fecundity and highest settlement success of the resulting brooded larvae. Finally, a phase of apparent senescence was observed for the largest individuals, characterised by decreases in most of the parameters measured. These data for mushroom corals provide the most direct estimates currently available of physiological, age-related trade-offs during the life history of a coral. The importance of energy allocation to reproduction led us to examine reproductive strategies and sex-allocation in the two species studied, revealing complex reproductive plasticity in F. fungites on the GBR, with female individuals releasing eggs, embryos, planulae or combinations of these. These unusual reproductive characteristics of the GBR F. fungites indicate previously unknown layers of complexity in the reproductive biology of corals and have implications for their adaptive potential across a wide geographical scale.